Biomechanical consequences of subtalar joint arthroereisis in treating posterior tibial tendon dysfunction: a theoretical analysis using finite element analysis. Issue 14 (26th October 2017) - Wong, Duo Wai-Chi; Wang, Yan; Chen, Tony Lin-Wei; Leung, Aaron Kam-Lun; Zhang, Ming
Abstract: Subtalar joint arthroereisis (SJA) has been introduced to control the hyperpronation in cases of flatfoot. The objective of this study is to evaluate the biomechanical consequence of SJA to restore the internal stress and load transfer to the intact state from the attenuated biomechanical condition induced by posterior tibial tendon dysfunction (PTTD). A three-dimensional finite element model of the foot and ankle complex was constructed based on clinical images of a healthy female (age 28 years, height 165 cm, body mass 54 kg). The boundary and loading condition during walking was acquired from the gait experiment of the model subject. Five sets of simulations (conditions) were completed: intact condition, mild PTTD, severe PTTD, mild PTTD with SJA, severe PTTD with SJA. The maximum von Mises stress of the metatarsal shafts and the load transfer along the midfoot during stance were analyzed. Generally, SJA deteriorated the joint force of the medial cuneonavicular and calcaneocuboid joints during late stance, while that of the metatarsocuneiform joints during early stance were over-corrected. Only the calcaneocuboid joint force at 45% stance demonstrated a trend of improvement. Besides, SJA exaggerated the increased stress of the metatarsals compared to the PTTD conditions, except that of the first metatarsal. Our study did not support the hypothesis that SJA can restore the internal load transfer and midfoot stress. SJA cannot compensate the salvage of midfoot stability attributed by PTTD and could be biomechanically insufficient to restore the biomechanical environment. Additional procedures such as orthotic intervention may be necessary.